Retrospective analysis of cattle poisoning in Argentina (2000-2013) - García, Juan Agustín (2017)
A retrospective analysis (2000 to 2013) of cattle poisoning caused by toxic plants and other compounds was carried out in the Pampas region of Argentina by the Animal Health Group of INTA-EEA, Balcarce. During this period, 1263 reports of diseases of different etiologies (infectious, parasitic, toxic, metabolic and miscellaneous) were recorded in cattle, by collecting anamnestic, clinical and pathological information. A toxic etiology was diagnosed in 21.1% of these reports. Iatrogenic poisoning caused by ionophores was the most frequently recorded etiology. Consumption of toxic plants (Wedelia glauca, Solanum glaucophyllum, among others), mycotoxins (Claviceps purpurea, Claviceps paspali, Epichloë coenophiala, among others), and plants producing cyanide and nitrates/nitrites were also commonly diagnosed. The high frequency of toxic episodes and the difficulties in their diagnosis by practitioners in our livestock production systems emphasizes the importance of this report.